505 Failed Femoral Nail with Significant Operative Technical Difficulty: A Practical Solution to Achieve Metalwork Extraction Using Conical Screw Remover. (12th October 2021) - Paluch, A; Clarke, A; Smith, S; Adams, S
Abstract: Introduction: There is a greater risk of delayed healing and revision surgery in atypical femoral fractures (AFFs). Although non-union in reamed intra-medullary (IM) nailing is relatively uncommon, it can lead to fracture of the nail and present a considerable challenge to the treating surgeon. Case Report: We present a case of AFF treated with IM nail fixation. Metalwork failure of the nail prompted removal of distal locking screws and plating of the fracture site at 8 months. Failure of the plate-bone interface 3 months later led to further revision surgery to remove the broken metalwork. We focus on the significant operative difficulty encountered during removal of the failed IM metalwork and provide a novel practical solution to overcome this particular challenge - insertion of a conical cannulated screw remover under fluoroscopy guidance to create an interference fit with the distal segment of the broken nail. Discussion: This case is an example of significant and unexpected intra-operative technical difficulty, requiring improvisation and teamwork to manage. We introduce an accessible and uncomplicated alternative to the existing techniques for removal of a broken femoral nail and in doing so hope to benefit peers and colleagues should they encounter similar difficulties in the future.